THE EFFECT OF LEVERAGE, ACCEPTABLE TURNOVER AND INVENTORY TURNOVER ON COMPANY PROFITABILITY - Kartika, Annisa Dwi; Hertati, Lesi; Munandar, Aris (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This study aims to determine the effect of leverage, accounts receivable turnover and inventory turnover on profitability in food and beverage industry companies listed on the IDX for 2019-2021. This research is quantitative in nature. The sample used consisted of 18 companies from a population of 26 food and beverage companies listed on the Indonesian Stock Exchange in 2019-2021. This study makes use of Indonesia Stock Exchange as a secondary data. The method of data analysis employed is panel data regression. The results showed that Profitability is a predictable growth or reduction in annual earnings. Significant profit capability indicates the company's potential to generate high profits, resulting in a rise in dividend payout. Hence, the potential to generate profits will influence the decision of investors to raise their capital investment in the business.